Effectiveness of KWL (Know-Want-Learn) Thinking Strategy to Learning Activity and Understanding of Living Creature Classification Concepts - Farida, Umi; Sri Iswari, Retno; Rini Indriyanti, Dyah (Journal of Innovative Science Education, 2020)
Science is a learning given at school. Learning strategy choices would influence to learning success. There is a need of creative and innovative strategy to improve learning activities and student conceptual understanding, such as by using KWL thinking strategy (Know-Want-Learn) assisted by video. This research aims to analyze learning activity and effectiveness of learning conceptual understanding at VII grade of a Public Junior High School in Nganjuk after being intervened by KWL thinking strategy assisted by video. This quasi experimental research design used pretest-posttest control group design with 64 students in which 32 of them grouped into control group while the remaining were grouped into experimental group. Technique of collecting data was simple random sampling. Experimental group student activity analysis results show 28 of them (87,50%) are categorized excellent and 4 of them (12,50%) sufficient. Meanwhile, the control group shows 11 of them (34,37%) categorized excellent and 21 of them (65,63%) categorized sufficient. Analysis of experimental and control group classical accomplishment met the effective criteria since it passed 75%. Classical accomplishment of completed experimental group's cognitive aspect reached 28 students (87,50%). Meanwhile, the control group reached 26 students (81,25%). The improvement of learning outcome was calculated by significance test or t-test. The result of control group’s t-test showed t-count 8,64 > t-table 2,03. The experimental group obtained t-count 11,12 > t-table 2,03. The improvement and accomplishment of experimental group was better than control group. Based on the results, it could be concluded that KWL thinking strategy assisted by video was effective to improve learning activity and VII graders’ conceptual understanding learning at a Public JHS in Nganjuk.